FINANCIAL ATTITUDE DAN FINANCIAL LITERACY TERHADAP TAX KNOWLEDGE PADA KAUM MILENIAL DI MALANG RAYA - Muhamad Bahrul Subakir; Jeni Susyanti; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this research is to determine the effect financial attitude and financial literacy on millennials tax knowledge in Malang, either simultaneous simultaneously. The dependent variable used in this study are Tax Knowledge. While the independent variables used in this study are Financial attitude and Financial literacy. The sample used in the study was a method is simple random sampling technique consisting of 100 respondents. Then the research data is processed using instrument test, classic assumption, multiple linear regression, and hypothesis testing, namely the f test and t test.The results of this study indicate that simultaneously, financial attitude and financial literacy have a significant effect on tax knowledge of millennials in Malang. As well as partially financial attitude and financial literacy also have a significant effect on tax knowledge among millennials in Malang. Keywords: Financial attitude, Financia literacy, Tax Knowledge and Millennials.